Caracterización química (N, P, K, pH y CE) del horizonte A, de los suelos en el campus La María del cantón Mocache - Castillo Burneo, Mónica Estefanía (2019)
The research project was carried out at the Quevedo State Technical University of the "La María" Campus, located at kilometer 7 and a half of the Via Quevedo-El Empalme in the province of Los Ríos. The main objective is the chemical characterization (N, P, K, pH and CE) of horizon A, of the soils on the Campus of "La Maria". Know what conditions Horizon A is currently in and reveal the disposition of nutrients in different places of agricultural use and do not cause variation in the soil. The specific objectives were: Determine the content of nitrogen (N), phosphorus (P), potassium (K). Evaluate electrical conductivity (EC) values. Set the pH value on the "A" horizon on the "La Maria" Campus. This research examined two phases with a three-month consideration, between sample collection and preparation and the laboratory phase where methodologies were used in the determination of the different variables. A fully randomized design (DCA) was used with 20 treatments and three repetitions in Horizon A. The results were analyzed in the InfoStat statistical program, and tested by Tukey with a 95% probability. When the average NH4+ was 18.68 ppm per scale it is classified as a low percentage of nitrogen; while the average phosphorus content was 6.15 ppm P-Olsen, which is classified as a low range of phosphorus; In addition the potassium content in the soil is found in a very high content with averages of 457.08 ppm K. The pH content (H2O and CaCl2) averaged 6.97 and 6.07 corresponding to the neutral and slightly acidic pH classification respectively. While in electrical conductivity, he gained 33.11 uS/cm on horizon A of the "The Mary" Campus. The lands showed marked variations in the nutritional content, however, the pH and salinity were below the critical levels of each crop. Keywords: Nitrogen, Phosphorus, Potassium, Laboratory, Soil.